Cell Therapy, Bispecific Antibodies and other Immunotherapies Against Cancer - Golubovskaya, Vita (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue in Cancers is focused on cell therapy, bispecific antibodies, and other immunotherapies against cancer. It includes reports on cell therapies such as CAR-NK cell therapies, and bispecific antibodies against multiple myeloma and B cell lymphoma. Immunotherapies against solid tumors include TGF-beta-PDL-1 fusion protein and EpCAM-CD3 bispecific antibody generated with mRNA-lipid nanoparticles (LNP) against colorectal tumors. The clinical studies ongoing with bi- and tri-specific T cell engager antibodies against solid tumors and advantages versus cell therapies are discussed. This Special Issue highlights novel approaches to cell therapies, bispecific antibodies, vaccines, and immunotherapies that will be interesting for cancer cell researchers, biologists, and oncologists.